Oldest evidence of tuberculosis in Argentina: A multidisciplinary investigation in an adult male skeleton from Saujil, Tinogasta, Catamarca (905–1030 CE) - (:unkn) unknown (Elsevier, 2020)
The Mycobacterium tuberculosis complex (MTC) has affected South American populations since ca. 200 years BCE. In Argentina, possible cases date from ca. 1000–1400 Common Era (CE). This paper describes the oldest (905–1030 CE) confirmed case of tuberculosis (TB) in a young adult male from Lomitas de Saujil (Tinogasta, Catamarca, Argentina). Osteolytic lesions on the bodies of the lower spine were macroscopically and radiographically identified. Bilateral new bone formation was seen on the visceral vertebral third of several ribs and in long bones, compatible with hypertrophic osteoarthropathy. Representative rib and hand bones gave profiles for MTC-specific C27–C32 mycocerosic acid lipid biomarkers; these were strongest in one heavily-lesioned lower rib, which also had MTC-diagnostic C76–C89 mycolic acids and positive amplification of MTC-typical IS6110 aDNA fragments. During the first millennium CE, the intense social interaction, the spatial circumscription of villages among the pre-Hispanic societies in the mesothermal valleys of Catamarca and the fluid contacts with the Eastern lowlands, valleys and puna, were factors likely to favor disease transmission. It is proposed that TB arrived from northern Chile and dispersed towards the northeast into the Yocavil valley, where several cases of TB infection were macroscopically identified for a later chronology.

Luna, L. H., Aranda, C. M., Santos, A. L., Donoghue, H. D., Lee, O. Y-C., Wu, H. H. T., Besra, G. S., Minnikin, D. E., Llewellyn, G., Williams, C. M. y Ratto, N. R. (2020). Oldest evidence of tuberculosis in Argentina: A multidisciplinary investigation in an adult male skeleton from Saujil, Tinogasta, Catamarca (905–1030 CE). Tuberculosis, 125, 101995.
Fil: Luna, Leandro Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Fil: Aranda, Claudia Marcela. Universidad de Buenos Aires. Facultad de Odontología. Cátedra de Endodoncia; Argentina
Fil: Santos, Ana Luisa. University of Coimbra. Department of Life Sciences. Research Centre for Anthropology and Health; Portugal
Fil: Donoghue, Helen D. University College London. Centre for Clinical Microbiology; Reino Unido
Keywords: Infectious diseases; Paleopathology; Pott´s disease; M. tuberculosis complex